OP0047 Baricitinib, an Oral Janus Kinase Inhibitor, in the Treatment of Rheumatoid Arthritis: Safety and Efficacy in Open-Label, Long-Term Extension Study. (23rd January 2014) - Taylor, P.; Genovese, M. C.; Keystone, E.; Schlichting, D.; Beattie, S.; Macias, W.
Abstract : Background: Baricitinib (formerly LY3009104/INCB028050) is a novel, oral inhibitor of JAK1 and JAK2 in the JAK-STAT signaling pathway being investigated as a treatment for rheumatoid arthritis (RA). In a phase 2b study, baricitinib treatment resulted in significant improvements in the signs and symptoms of RA versus placebo over 12 weeks, and these responses were maintained or improved for an additional 12 weeks of blinded treatment 1 . Objectives: To report 52 week safety and efficacy findings in a snapshot of an open label extension of the phase 2b study. Methods: Patients (pts) were initially randomized to placebo (PBO) or 1of 4 once-daily (QD) baricitinib doses (1, 2, 4, or 8 mg) for 12 wks. Pts assigned to 2 mg, 4 mg or 8 mg continued assigned treatment and pts assigned to placebo or 1 mg were reassigned to 4 mg QD or 2 mg BID for an additional 12 weeks of blinded treatment. In the open label portion of the study, pts in 8 mg group continued to receive 8 mg QD and all other pts received 4 mg QD. Doses could be escalated to 8 mg QD at 28 or 32 weeks at the investigator's discretion when >6 tender and swollen joints were present. Analyses reported here include data through 52 weeks for pts treated in the open-label extension (non-responder imputation used for discontinued pts). Results: Of the 212 pts eligible to participate, 201(95%) pts entered the open label extension, 184 patients completed 52 weeks of treatment, 15 pts discontinued, and 2 pts had not yet completed 52 weeks. Among pts who remained on 4 mg (n=108), TEAEs occurred in 57 (53%), SAEs in 14 (13%), infections in 34 (31%) and serious infections in 4 (4%). Among pts who received 8 mg at any time (n=93), TEAEs occurred in 59 (63%), SAEs in 8 (9%), infections in 37 (40%) and serious infections in 2 (2%). No opportunistic infections or TB cases were observed. There was one death due to myocardial infarction in the 8 mg group. Among all pts combined in the open label extension, the proportions of pts achieving ACR20, ACR50, ACR70, CDAI Remission, SDAI Remission, DAS28CRP≤3.2, DAS28CRP<2.6, DAS28ESR≤3.2, DAS28CRP<2.6 or the ACR/EULAR Boolean remission at the start of the open label extension (week 24) were similar or increased at week 52 (Table). This increase was mainly due to enhanced clinical responses following dose escalation in patients who initially received PBO, 1 mg or 2 mg QD. Conclusions: Among pts completing 52 weeks of a phase 2b study, clinical improvements observed at week 24 were maintained or improved during the open label extension. In addition, safety signals observed over the open label extension were consistent with previously reported results of baricitinib. References: Genovese et al. Arthritis and Rheumatism, 2012, Vol 63 supplment 10: 2487 Disclosure of Interest: P. Taylor Grant/research support from: Merck, UCB, Celgene, AstraZeneca, GSK, Consultant for: Abbott, BMS, Centocor, Eli Lilly, M. Genovese Grant/research support from: Eli Lilly, Consultant for: Eli Lilly, E. Keystone Grant/research support from: Abbott; Amgen; AstraZeneca; BMS, F. Hoffmann-La Roche, Janssen, Eli Lilly, Novartis, Pfizer, UCB, Consultant for: Abbott, AstraZeneca, Biotest, BMS, F. Hoffmann-LaRoche, Genentech, Janssen, Eli Lilly, Merck, Nycomed, Pfizer, UCB, Speakers bureau: AstraZeneca, BMS, F. Hoffmann-LaRoche, Janssen, Pfizer, UCB, Amgen, Abbott, D. Schlichting Shareholder of: Eli Lilly, Employee of: Eli Lilly, S. Beattie Shareholder of: Eli Lilly, Employee of: Eli Lilly, W. Macias Shareholder of: Eli Lilly, Employee of: Eli Lilly